Radiação gama na conservação de caqui 'Giombo', destanizado e frigoarmazenado - Vieites, Rogério Lopes [UNESP] (2012)
The persimmon presents a short harvest, being necessary to extend his commercialization period using appropriate storage techniques. The purpose of this work was to evaluate the use of the gamma radiation in the postharvest quality 'Giombo' persimmons without adstringency. Fruits were harvest middleripe, with approximately 50% of the green coloration and were submitted to the process of astringency removal, packed in expanded polystyrene (EPS) trays, covered by low densidy polyethylene (LDPE) plastic film and submitted the gamma radiation (60Co). The fruits were stored for 35 days, under refrigeration (0±0,5 °C and 85 ± 0,5% of relative humidity). The evaluated treatments were: T1 - 0.0 kGy; T2 - 0.3 kGy; T3 - 0.6 kGy; T4 - 0.9 kGy; T5 - 1.2 kGy. The evaluated analyses every 7 days were: weight loss, respiratory activity, soluble solids (SS), ascorbic acid content, acidity titulável (AT), and relation SS/AT. The fruits submitted to the 0.6kGy presented the percentile smallest of weight loss and smaller Co2 production along the experimental period. The SS and AT content stayed stable and without difference among the irradiation applied. The treatments with 0.3 kGy e 0.6 kGy were the most effective in the maintenance of the persimmon firmness values. For the ascorbic acid content was observed reduction along the experimental period being the smallest values presented for the largest irradiation dose (1,2 KGy).